2014
DOI: 10.1007/s00264-014-2509-5
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular revision arthroplasty using trabecular titanium implants

Abstract: Purpose The aim of this study was to evaluate early results of acetabular revisions of total hip replacement using fully cementless trabecular titanium (TT) acetabular modular implants (Delta Trabecular Titanium, Limacorporate, Udine, Italy). Methods Between March 2009 and May 2012 TT was used in 81 revisions. The mean age at the time of revision was 68 years (32-84 years). There were nine patients revised for type 1, 11 for type 2A, 27 for type 2B, six for type 2C, 15 for type 3A and 13 for type 3B acetabular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
53
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 30 publications
6
53
0
2
Order By: Relevance
“…Ideally, the porous surface and the main body of the implant should be fabricated integrally as one piece. For this purpose, additive manufacturing methods with metal powders have been recently introduced to the field of orthopedics, and hip implants fabricated by electron beam melting are already in clinical use 2) . Selective laser melting (SLM) technology [3][4][5] is one of the additive manufacturing methods available for the formation of metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the porous surface and the main body of the implant should be fabricated integrally as one piece. For this purpose, additive manufacturing methods with metal powders have been recently introduced to the field of orthopedics, and hip implants fabricated by electron beam melting are already in clinical use 2) . Selective laser melting (SLM) technology [3][4][5] is one of the additive manufacturing methods available for the formation of metal implants.…”
Section: Introductionmentioning
confidence: 99%
“…Wymienione właściwości porowatego tytanu spowodowały, że wykonane z niego panewki oraz uzupełnienia znalazły szerokie i efektywne zastosowanie w aloplastykach rewizyjnych [15][16][17][18][19][20]. W związ-ku z tak dobrymi wynikami zastosowania porowatego tytanu w realoplastykach postanowiliśmy użyć go również w zabiegach pierwotnych, w których niezbędne było uzupełnienie ubytków kotnych panewki.…”
Section: Wstępunclassified
“…Due to the above properties of trabecular titanium, titanium acetabula and implants have been widely and effectively used in revision arthroplasty [15][16][17][18][19][20]. In view of such positive outcomes of trabecular titanium use for revision arthroplasty, we decided to employ it in those primary procedures where it was necessary to fill acetabular defects.…”
Section: Introductionmentioning
confidence: 99%
“…Due to lack of resources, the initial treatment for these types of defects was structural allografts (5,6). Later on, newer technology allowed the use of cages (7,8), jumbo cups (9-11), and most recently, acetabular augments have been added to our armamentarium (12,13). All these treatment options have been used for filling acetabular defects, but consensus for superiority of one method over others has not been reached.…”
Section: Introductionmentioning
confidence: 99%
“…Following cage reconstruction, there can be increased bone loss and structural failure (16), and elevation of the center of rotation can occur after using jumbo cups (17,18). Previous studies have reported on the use and outcomes of trabecular metal acetabular augments for the reconstruction of acetabular defects (13). However, no study has been conducted evaluating augmentation of acetabular defects using tritanium acetabular wedge augments.…”
Section: Introductionmentioning
confidence: 99%